Investigating the role of Y-box binding protein 1 in medulloblastoma tumour progression and drug resistance - Taylor, Louisa (2022)
Introduction: Medulloblastoma relapse represents the most significant unmet clinical challenge in childhood cancer. In spite of this, our understanding of the molecular biology of relapsed medulloblastoma is limited. Evidence is emerging, however, that the biology of medulloblastoma at relapse differs significantly from the disease at diagnosis. Such genetic divergence may arise through the emergence and expansion of a therapy-resistant sub-population of cells. Thus, the identification of targets that either mark therapy resistant cell populations, or drive the proliferation of resistant medulloblastoma cells, may improve treatment strategies for relapsed disease. YB-1, a transcription factor encoded by the YBX1 gene, has been extensively researched in non-CNS tumours where elevated expression is associated with tumour progression and drug resistance. However, little is known regarding the significance of YB-1 in paediatric brain tumours. This study, therefore, set out to examine the functional role of YB-1 in medulloblastoma tumourigenesis. Particular attention was paid to the multi-drug transporter ABCB1, a putative YB-1 target, which our studies have shown to be associated with cancer cell therapy resistance and high-risk medulloblastoma.